Private debt, public debt, and capital misallocation - Behzod Alimov (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2019)
Does finance facilitate efficient allocation of resources? Our aim in this paper is to find out whether increases in private and public indebtedness affect capital misallocation, which is measured as the dispersion in the return to capital across firms in different industries. For this, we use a novel dataset containing industrylevel data for 18 European countries and control for different macroeconomic indicators as potential determinants of capital misallocation. We exploit the within-country variation across industries in such indicators as external finance dependence, technological intensity, credit constraints and competitive structure, and find that private debt accumulation disproportionately increases capital misallocation in industries with higher financial dependence, higher R&D intensity, a larger share of credit-constrained firms and a lower level of competition. On the other hand, we fail to find any significant and robust effect of public debt on capital misallocation within our country-sector pairs. We believe the distortionary effects of private debt found in our analysis needs a deeper theoretical investigation.
urn:nbn:de:gbv:3:2-115344
Keywords: D24; D61; E44; F34; H63; O47; 330; private debt; public debt; capital misallocation; productivity